QoSHVCP: Hybrid Vehicular Communications Protocol with QoS Prioritization for Safety Applications. (17th April 2012) - Mostafa, Ahmad; Vegni, Anna Maria; Oliveira, Talmai; Little, Thomas D. C.; Agrawal, Dharma P.
Abstract : This paper introduces a hybrid communication paradigm for achieving seamless connectivity in Vehicular Ad hoc Networks (VANETs), wherein the connectivity is often affected by changes in the dynamic topology, vehicles' speed, as well as the traffic density. Our proposed technique named QoS-oriented Hybrid Vehicular Communications Protocol (QoSHVCP) exploits both existing network infrastructure through a Vehicle-to-Infrastructure (V2I), as well as a traditional Vehicle-to-Vehicle (V2V) connection that could satisfy Quality-of-Service requirements. QoSHVCP is based on a V2V-V2I protocol switching algorithm, executed in a distributed fashion by each vehicle and is based on the cost function for alternative paths each time it needs to transmit a message. We utilize time delay as a performance metric and present the delay propagation rates when vehicles are transmitting high priority messages via QoSHVCP. Simulation results indicate that simultaneous usage of preexisting network infrastructure along with intervehicular communication provide lower delays, while maintaining the level of user's performance. Our results show a great promise for their future use in VANETs.